2019
DOI: 10.5897/err2018.3670
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tablet use on students success in English as a Foreign Language (EFL) grammar classroom

Abstract: Integration of tablets in teaching English as a Second or Foreign language has been popular in recent years. However, there is limited evidence to prove the effect of tablet use on the acquisition of specific language skills. This paper aims to investigate the impact of tablet use on students' mastery of grammar skills. In order to answer the research questions, an experimental pretest-posttest with a control group design was employed at a private university in Turkey. The pre-test scores of both groups were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The recent study by Bilotserkovets and Fomenko (2022) also shows that the implementation of mobile devices and applications was very attractive and practical, as 96.1% of learners preferred to combine learning with the use of digital devices such as smartphones and tablets in everyday life. Kayapinar et al (2019) and Lin (2014) found in their studies that the changes because of the use of educational technology in the classroom could also lead to an overall statistically significant difference in achievement scores.…”
Section: Results From the Lesson Observationmentioning
confidence: 98%
See 2 more Smart Citations
“…The recent study by Bilotserkovets and Fomenko (2022) also shows that the implementation of mobile devices and applications was very attractive and practical, as 96.1% of learners preferred to combine learning with the use of digital devices such as smartphones and tablets in everyday life. Kayapinar et al (2019) and Lin (2014) found in their studies that the changes because of the use of educational technology in the classroom could also lead to an overall statistically significant difference in achievement scores.…”
Section: Results From the Lesson Observationmentioning
confidence: 98%
“…Chartrand (2016) adds that multimedia capability is another advantage of using mobile devices, and in our case, DLPs allow learners to further practise their foreign language in different ways, including by watching videos or listening to how natives speak the language. In this way, learners have instant access to individual research, providing a huge knowledge base (Kayapinar et al 2019). DLP-based exercises can instantly assess learners' answers and provide detailed explanations of the grammar point in question, giving learners independence, as they do not have to rely solely on the teacher's explanations (Kayapinar et al 2019).…”
Section: Results From the Lesson Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heift & Vyatkina (2017) claim that technology-based approaches were introduced and have been implemented in teaching grammar since around the 1960s. There are many different types of technology-based or technology-assisted approaches based on the platforms they use such as computer-assisted language learning (which offers wide ranges of resources, instructions, feedbacks, practice exercises for learners to improve grammar and grammatical accuracy (Dikli & Bleyle, 2014;Li et al, 2017)), mobile/tablet-assisted language learning (refers to using games developed for mobile or tablets to motivate students and as a result improve their grammar efficiency (Chen, et al, 2019;Kayapinar et al, 2019;Rachels & Rockinson-Szapkiw, 2018), virtual-assisted language learning (in which students are provided with records or nativelike environment to practice their language in general and according to Chen (2016) it improves learner's grammar and syntax knowledge along with other linguistics aspects like phonetic and morphologic knowledge at a higher level), or robot-assisted language learning (in which the effectiveness of robots in the role of tutors and assistance of teachers in teaching grammar is proved by Lee et al (2011) when they claim that this approach motivates students, boosts their confidence, satisfaction and interest).…”
Section: Technology-based Grammar Teaching and Learningmentioning
confidence: 99%
“…The study fits into this general area of innovation that various authors claim as essential (Galván-Malagón & López-Pérez, 2017;Lezama, 2014;McGinity, 2002). Other studies have been done in this area (as in Cai, 2012;Kayapinar et al, 2019;Öztürk, 2018;Zhang & Nouri, 2018) but never in a private school in central Mexico. The study may then contribute to previous work because it mainly focuses on the use of a specific tablet, the iPad.…”
Section: Introductionmentioning
confidence: 99%